Menelisik Conscientiousness dan Toleransi Ambiguitas terhadap Kecenderungan Pengambilan Resiko pada Pelaku UMKM di Era New Normal (Jurnal Psikologi Integratif, 2024)
In challenging situations like the Covid-19 pandemic, MSME entrepreneurs are among the affected parties. However, the development and efforts to recover have become a primary demand for MSME entrepreneurs to survive in difficult circumstances. Coupled with changes in consumer habits and preferences, known as the "new normal," it has become a new era that forces MSME entrepreneurs to face a situation full of ambiguity. This study employs purposive sampling to select participants, specifically MSME actors in the city of Palembang who reside in the area, resulting in a total of 150 MSME participants with a variety of product types.  This research discusses how the risk-taking propensity of MSME entrepreneurs is influenced by their tolerance ambiguity and conscientiousness. The findings revealed a significant role of tolerance ambiguity in risk-taking propensity (p
Keywords: Ambiguity tolerance; Conscientiousness; Risk taking propensity; New Normal